2013
DOI: 10.4025/actascitechnol.v36i1.18995
|View full text |Cite
|
Sign up to set email alerts
|

<b>Imbalances in the hardness/alkalinity ratio of water and Nile tilapia’s growth performance</b> - doi: 10.4025/actascitechnol.v36i1.18995

Abstract: ABSTRACT. The present work determined the effects of water with unbalanced calcium hardness/total alkalinity (CH/TA) ratio on Nile tilapia growth performance. Two unbalanced CH/TA ratios were tested for 8 weeks using one indoor system with 30 circular polyethylene 100 L tanks and one outdoor system with 36 circular polyethylene 250 L tanks. The factors and their specific levels tested were the total alkalinity of water (TA; 50 and 100 mg L -1 CaCO 3 ) and the CH/TA ratio of water (CH/TA; 1/2, 1/1 and 5/1). In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…Temperature was maintained at optimal performance values for Nile tilapia (Silva et al, 2019). In terms of hardness values and the hardness: alkalinity ratio were within values that do not affect the zootechnical performance of tilapia juveniles, according to the literature (Cavalcante et al, 2012;2014).…”
Section: Resultssupporting
confidence: 54%
“…Temperature was maintained at optimal performance values for Nile tilapia (Silva et al, 2019). In terms of hardness values and the hardness: alkalinity ratio were within values that do not affect the zootechnical performance of tilapia juveniles, according to the literature (Cavalcante et al, 2012;2014).…”
Section: Resultssupporting
confidence: 54%
“…The dolomitic limestone (CaMgCO 3 ) added to both systems in the present study in order to deliver adequate water alkalinity also increased total hardness as well as its electric conductivity, which is commonly used to assess nutrient availability in aquatic ecosystems (Boyd, 2015). Holanda Cavalcante et al (2014) suggest that fish handling is safer and animal performance is better in water with total alkalinity to hardness ratio of 1:1 (between 55 and 150 mg/L of CaCO 3 ). Although these parameters varied significantly between production systems during the experiment due to the daily water renewal in CW, the supply of CaMgCO 3 maintained the proportion of 1:1 in both systems.…”
Section: Discussionmentioning
confidence: 99%
“…The provision of ready-made antibody molecules can help stimulate the non-specific immune system in fish. The normal range for water quality variables in tilapia cultivation is temperature 25°C–32°C, pH 6.5–8.5, dissolved oxygen ≥3 mg/L [ 45 ], TAN for rearing red tilapia 0.17–3.87 mg/L [ 46 ], and TDS of <1000 ppm [ 47 ]. The water quality data showed that fish mortality was not related to poor water quality.…”
Section: Discussionmentioning
confidence: 99%